Preparation method of high-performance composite membrane easy for large-scale preparation

Through the combination of hydroxyl-terminated PDMS, crosslinking agent and catalyst and multiple coating heat treatment technology, a high-performance composite film was prepared, which solved the problems of low separation factors and insufficient flux of the existing composite film, and achieved separation factors and The significant increase in flux has promoted the industrial application of composite membranes.

CN119186290APending Publication Date: 2024-12-27CHINA UNIV OF MINING & TECH (BEIJING)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410875088.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-02
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing composite membrane materials have low separation factors in permeation vaporization and VOCs recovery, and the flux is limited when increasing the separation factors, making it difficult to achieve industrial application.

Method used

Using hydroxyl-terminated PDMS as raw material, the cast film liquid is prepared by preparing it with soluble solvents, crosslinking agents and catalysts, and using ultrafiltration membranes as support layers. High-performance composite membranes are prepared through multiple coatings and heat treatments to improve separation factors and flux.

Benefits of technology

The separation factor and permeability flux of the composite membrane have been significantly improved. The separation factor for permeability and VOCs recovery has increased from about 8 to nearly 40, and the permeability flux has also increased, showing the industrial application potential of this membrane-making technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186290A_ABST
    Figure CN119186290A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-performance composite membrane easy to prepare on a large scale, which comprises the following steps: dissolving hydroxyl-terminated PDMS in a solvent, adding a cross-linking agent and a catalyst to prepare a membrane casting solution, taking an ultrafiltration membrane as a base membrane, scraping the PDMS membrane casting solution with a certain concentration on the ultrafiltration membrane, continuously scraping the membrane after the membrane casting solution is preliminarily cured, and repeating the steps for no less than one time to obtain the high-performance composite membrane. And then performing heat treatment to form the high-performance composite film. Under the condition that the separation performance of the separation membrane material is limited, the separation performance of the composite membrane can be greatly enhanced by coating the membrane casting solution for multiple times, the separation factor is greatly increased, and meanwhile, the permeation flux is also improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a high-performance composite membrane which is easy to prepare on a large scale, and in particular to a method for preparing a composite membrane through which organic matter can preferentially pass. Background Art

[0002] With the advent of the global energy crisis, humans have been seeking new energy sources that can replace non-renewable energy sources such as oil. Biomass fuel ethanol can replace traditional oil energy to a certain extent, while greatly reducing environmental pollution. It is a new energy source with great potential. At present, developed countries such as Europe and the United States have replaced part of the oil with bioethanol to varying degrees, and are committed to large-scale production of fuel ethanol.

[0003] In the process of preparing ethanol by biological fermentation, as the concentration of ethanol in the fermentation tank increases, the activity of yeast is inhibited and the substrate cannot continue to be fermented and utilized. Pervaporation can be used to selectively separate the ethanol in the fermentation broth, thereby avoiding the inhibitory effect of high concentration ethanol on yeast and improving the utilization rate of the substrate. The main factor that determines the performance of pervaporation is the membrane material. However, so far, the types of polymer preferential alcohol permeation membrane materials are limited, mainly PDMS, polytrimethylsilyl-1-propyne (PTMSP), fluorinated silicone rubber and polyether block amide (PEBA) and other materials. Among them, PDMS has relatively good comprehensive performance and is the most studied material at present. The separation performance of other materials is insufficient or the stability is not enough (PTMSP). According to reports, the separation factor of pure PDMS membrane for ethanol-water solution system is mostly between 6-9, and the permeation flux is 500-3000g·m -2 ·h -1 In general, the separation factor is low. When the ethanol concentration in the raw liquid is 6%, the ethanol concentration in the permeate is only 34% when the separation factor is 9. If the separation factor of the membrane can be greatly improved, the concentration of ethanol in the permeate can be effectively increased, the amount of water permeation can be reduced, and a large amount of operating energy consumption can be saved.

[0004] The main methods to improve the separation factor of PDMS composite membranes include surface modification, filling with molecular sieves, metal organic framework materials (MOF) and covalent organic framework materials (COF). For example, filling with silane coupling agent-modified molecular sieve Silicate-1 can increase the separation factor to about 15-20, but the permeation flux is greatly reduced to 100g·m -2 ·h -1 However, such a low permeation flux makes it have no industrial application prospects. Filling MOF has little effect on the permeation flux of the composite membrane, but the separation factor is limited.

[0005] As the most important material for pervaporation alcohol permeation membrane, PDMS is also used for the recovery of volatile organic compounds (VOCs). The sources of VOCs include many industries such as petroleum refining, oil and gas storage and transportation, chemical production, and coatings. At present, the main methods for industrial VOCs recovery are membrane separation, adsorption, absorption, condensation, etc. Among them, membrane separation has the advantages of small footprint, low energy consumption, high efficiency, simple operation, and less secondary pollution. Since 2001, gas membrane separation technology has been promoted in China and has been industrially applied in many industries. For example, nearly 90% of small-scale polyethylene companies currently use membrane separation propylene recovery devices. In the organic gas recovery membrane technology, the development of high-performance membrane materials has always been one of the focuses. The gas separation membrane should meet the requirements of high permeation rate, high selectivity, ability to withstand large pressure differences, and stable operation under complex environments. The separation factor of the currently used silicone rubber materials (PDMS, etc.) for organic gases is relatively low, only about 10-15, and there is still a lot of air in the permeated gas, which needs further treatment.

[0006] Whether it is pervaporation to preferentially permeate alcohol or VOCs recovery, there is an urgent need to improve the separation factor of the membrane. However, the membrane materials that can be industrially applied in these two directions are mainly PDMS, and the current technology cannot effectively improve the separation factor of the composite membrane with limited impact on the flux. How to provide a preparation method for high-performance composite membranes that is easy to prepare on a large scale based on existing membrane materials through the innovation of membrane making technology, greatly improve the separation factor of the composite membrane, and promote the industrial application of the composite membrane is a problem that needs to be solved urgently. Summary of the invention

[0007] The object of the present invention is to provide a method for preparing a high-performance composite membrane that is easy to prepare on a large scale, greatly improving the separation factor of the composite membrane while improving the flux, or having little effect on the flux.

[0008] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0009] The present invention provides a method for preparing a high-performance composite membrane that is easy to prepare on a large scale, comprising the following steps:

[0010] (1) dissolving the hydroxyl-terminated PDMS in a soluble solvent to form solutions of different concentrations, and adding a crosslinking agent and a catalyst to prepare a casting solution;

[0011] (2) using an ultrafiltration membrane as a support layer, coating the casting solution in step (1) on the support layer at a certain thickness, leaving it for a certain period of time to allow the solvent to evaporate and initially solidify; subsequently, coating the casting solution in step (1) on the initially solidified membrane at a certain thickness, leaving it for a certain period of time at room temperature to allow the solvent to evaporate and initially solidify, repeating this step for at least one time, and the concentrations of the casting solutions used in different batches of coating may be the same or different;

[0012] (3) The membrane obtained in step (2) is heat treated for more than 0.5 hours to fully crosslink it to obtain a high-performance composite membrane.

[0013] Preferably, the crosslinking agent used in step (1) is tetraethyl orthosilicate, phenyltrimethoxysilane, octyltrimethoxysilane, n-octyltrichlorosilane, vinyltrimethoxysilane, methyltrimethoxysilane, γ-aminopropyltriethoxysilane or hydrogenated silicone oil.

[0014] Preferably, the catalyst used in step (1) is an organotin catalyst.

[0015] Preferably, the ultrafiltration membrane used in step (1) is made of any one of polyvinylidene fluoride, polytetrafluoroethylene, polysulfone, polyimide, polyetherimide, polyacrylonitrile or polyetheretherketone.

[0016] Preferably, the heat treatment temperature in step (3) is between 40 and 120°C.

[0017] When composite membranes are used for pervaporation or VOCs recovery, their separation performance mainly has two indicators, namely, permeation flux and separation factor.

[0018] 1) Composite membrane permeation flux is used to characterize the rate at which the permeating components penetrate the membrane. It refers to the amount of the mixture components that diffuse through the membrane per unit area per unit time. Its definition is:

[0019]

[0020] Where J refers to the permeate flux, and the units for pervaporation and VOCs recovery are g·m -2 ·h -1 and L·m -2 ·h -1 ; Q refers to the flow rate of permeating gas, and the units for pervaporation and VOCs recovery are g·h -1 and L.h -1 ; A is the effective membrane area (m 2 ).

[0021] 2) The separation factor represents the separation effect of the composite membrane, and its definition is:

[0022]

[0023] When used for pervaporation, x i 、x j is the mass fraction of ethanol and water in the raw material solution, y i ,y j is the mass fraction of ethanol and water in the permeate; when used for VOCs recovery, xi 、x j is the volume fraction of organic gas and nitrogen in the raw gas, y i ,y j is the volume fraction of organic gas and nitrogen in the permeate gas. Regardless of pervaporation or VOCs recovery, the larger the separation factor β, the better the separation effect.

[0024] The present invention provides a method for preparing a high-performance composite membrane that is easy to prepare on a large scale, using hydroxyl-terminated PDMS as a raw material, dissolving it in a soluble solvent, and adding a cross-linking agent and a catalyst to prepare a casting liquid; then, using an ultrafiltration membrane as a support layer, passing the casting liquid through a large-scale production equipment such as a casting machine at a certain thickness, coating the casting liquid on the support layer, leaving it for a period of time until the solvent evaporates and initially solidifies; then coating the casting liquid again, volatilizing the solvent, and solidifying, repeating for no less than 1 time; finally, through heat treatment, the final product, a high-performance composite membrane, is obtained. The results of the embodiment show that the method for preparing a high-performance composite membrane that is easy to prepare on a large scale provided by the present invention, the high-performance composite membrane obtained, is used for preferential ethanol removal by pervaporation, and the separation factor is increased from about 8 to nearly 40, and the permeation flux is improved to a certain extent; for VOCs recovery, the separation factor is increased from about 10 to 36.6, and the permeation flux is also improved to a certain extent, showing the outstanding advantages of the membrane making technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 , Figure 2 They are scanning electron microscope images of the surface and cross section of the PDMS composite membrane of the present invention, Figure 3 For the energy spectrum (EDX) analysis of the cross section of the PDMS composite membrane of the present invention, a composite membrane coated with the casting solution twice was used. DETAILED DESCRIPTION

[0026] In order to deepen the understanding of the present invention, the present invention will be further described in detail below in conjunction with examples. The examples are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention.

[0027] Example 1

[0028] Dissolve the hydroxyl-terminated PDMS in n-heptane, then add the crosslinking agent ethyl orthosilicate and the catalyst dibutyltin dilaurate in sequence, PDMS: ethyl orthosilicate: dibutyltin dilaurate = 100:20:3. Prepare casting solutions with different PDMS concentrations. Vacuum degas the casting solution and set aside.

[0029] Using a casting solution with a PDMS concentration of 3%, and a polyvinylidene fluoride ultrafiltration membrane as the support layer, the film was scraped on a casting machine at a thickness of 60 microns, and the scraped membrane was placed at room temperature for 10 minutes to allow the n-heptane to evaporate and the casting solution to initially solidify; then, the film was scraped with a casting solution with a PDMS concentration of 15%, and the film was placed for 2 hours to allow the heptane to evaporate and the casting solution to solidify; finally, the obtained membrane was heat treated at 100°C for 2 hours to fully cross-link the PDMS and obtain a high-performance composite membrane. A pervaporation permeation experiment was carried out using a 6% ethanol aqueous solution as the raw material. When the temperature was 61°C, the separation factor was 14.3 and the permeation flux was 3622g·m -2 ·h -1 , the ethanol concentration in the permeate is 47.5%.

[0030] Example 2

[0031] The preparation method of the casting liquid is the same as that of Example 1. A casting liquid with a PDMS concentration of 3% is used, and a polyvinylidene fluoride ultrafiltration membrane is used as a support layer. The film is scraped at a thickness of 60 microns on a casting machine, and the scraped film is placed at room temperature for 10 minutes to allow the n-heptane to volatilize and the casting liquid to initially solidify; then, a casting liquid with a PDMS concentration of 9% is used to continue scraping the film, and the heptane is volatilized for 10 minutes and the casting liquid is initially solidified; a casting liquid with a PDMS concentration of 3% is used to continue scraping the film, and the film is placed at room temperature for 10 minutes to allow the heptane to volatilize and the casting liquid to initially solidify, and this step is repeated once more. The membrane is placed for another 2 hours to allow the heptane to volatilize, and finally the obtained membrane is heat treated at 80°C for 2 hours to fully cross-link the PDMS to obtain a high-performance composite membrane. A pervaporation alcohol permeation experiment was carried out using a 6% ethanol aqueous solution as the raw material liquid. When the temperature was 61°C, the separation factor was 35.6 and the permeation flux was 3358g·m -2 ·h -1 , the ethanol concentration in the permeate is 69.2%.

[0032] Example 3

[0033] The preparation method of the casting liquid is the same as that of Example 1. A casting liquid with a PDMS concentration of 3% is used, and a polyvinylidene fluoride ultrafiltration membrane is used as a support layer. The film is scraped at a thickness of 60 microns on a casting machine, and the scraped film is placed at room temperature for 12 minutes to allow the n-heptane to volatilize and the casting liquid to initially solidify; then, a casting liquid with a PDMS concentration of 6% is used to continue scraping the film, and the heptane is volatilized for 10 minutes and the casting liquid is initially solidified; a casting liquid with a PDMS concentration of 3% is used to continue scraping the film, and the film is placed at room temperature for 12 minutes to allow the heptane to volatilize and the casting liquid to initially solidify, and this step is repeated twice. The membrane is placed for another 2 hours to allow the heptane to volatilize, and finally, the obtained membrane is heat treated at 100°C for 2 hours to fully cross-link the PDMS to obtain a high-performance composite membrane. A pervaporation alcohol permeation experiment was carried out using a 6% ethanol aqueous solution as the raw material liquid. When the temperature was 61°C, the separation factor was 39.3 and the permeation flux was 3156g·m-2 ·h -1 , the ethanol concentration in the permeate is 71.3%.

[0034] Example 4

[0035] Dissolve the hydroxyl-terminated PDMS in toluene, and then add the crosslinking agent vinyl trimethoxysilane and the catalyst dibutyltin dilaurate in sequence, PDMS: vinyl trimethoxysilane: dibutyltin dilaurate = 100:20:3. Prepare casting solutions with different PDMS concentrations. Vacuum degas the above solutions and set aside.

[0036] Using a casting solution with a PDMS concentration of 4%, and a polyvinylidene fluoride ultrafiltration membrane as the support layer, the film was scraped on a casting machine at a thickness of 100 microns. The scraped membrane was placed at room temperature for 10 minutes to allow the n-heptane to evaporate and the casting solution to initially solidify; then, the film was scraped again using a casting solution with a PDMS concentration of 16%, and the film was placed for 10 hours to allow the heptane to evaporate; finally, the obtained membrane was heat treated at 60°C for 10 hours to fully cross-link the PDMS and obtain a high-performance composite membrane. The prepared composite membrane was used to test the mixed gas separation performance. When the propane volume fraction in the mixed gas was 24%, the inlet temperature was 25°C, and the inlet pressure was 0.20MPa, the permeation flux was 420.3L·m -2 ·h -1 , the separation factor for propane is 20.5.

[0037] Example 5

[0038] The method for preparing the casting solution is the same as that in Example 4.

[0039] Using a casting liquid with a PDMS concentration of 4%, and a polyvinylidene fluoride ultrafiltration membrane as the support layer, the film was scraped on a casting machine at a thickness of 100 microns. The scraped membrane was placed at room temperature for 10 minutes to allow the n-heptane to evaporate and the casting liquid to initially solidify; then, the film was continued to be scraped using a casting liquid with a PDMS concentration of 4%, and the heptane was volatilized for 10 minutes and the casting liquid was initially solidified. This step was repeated 3 times. The membrane was placed for another 10 hours to allow the heptane to evaporate. Finally, the obtained membrane was heat treated at 120°C for 1 hour to fully cross-link the PDMS and obtain a high-performance composite membrane. The prepared composite membrane was used to test the mixed gas separation performance. When the propane volume fraction in the mixed gas was 24%, the inlet temperature was 25°C, and the inlet pressure was 0.20MPa, the permeation flux was 387.5L·m -2 ·h -1 , the separation factor for propane is 36.6.

[0040] Comparative Example 1

[0041] Dissolve the hydroxyl-terminated PDMS in n-heptane, and then add the crosslinking agent ethyl orthosilicate and the catalyst dibutyltin dilaurate in sequence, PDMS: ethyl orthosilicate: dibutyltin dilaurate = 100:20:3. Prepare casting solutions with different PDMS concentrations. Vacuum degas the above casting solutions and set them aside. Use a casting solution with a PDMS concentration of 18%, use a polyvinylidene fluoride ultrafiltration membrane as the support layer, and scrape the film on a casting machine at a thickness of 60 microns. Place the scraped membrane at room temperature for 2 hours to allow the heptane to evaporate and the casting solution to solidify. Subsequently, heat treat the resulting membrane at 100°C for 2 hours to fully crosslink the PDMS. Use a 6% ethanol aqueous solution as the raw material for a pervaporation alcohol permeation experiment. When the temperature is 61°C, the separation factor is 8.2 and the permeation flux is 2252g·m -2 ·h -1 , the ethanol concentration in the permeate was 34%.

[0042] Comparative Example 2

[0043] Dissolve the hydroxyl-terminated PDMS in toluene, and then add the crosslinking agent vinyl trimethoxysilane and the catalyst dibutyltin dilaurate in sequence, PDMS: vinyl trimethoxysilane: dibutyltin dilaurate = 100:20:3. Prepare casting solutions with different PDMS concentrations. Vacuum degas the above solutions and set aside.

[0044] Using a casting solution with a PDMS concentration of 20%, and a polyvinylidene fluoride ultrafiltration membrane as the support layer, the film was scraped on a casting machine at a thickness of 100 microns, and the scraped membrane was placed at room temperature for 10 hours to allow the heptane to volatilize; finally, the resulting membrane was heat treated at 60°C for 4 hours to fully cross-link the PDMS. The prepared composite membrane was used to test the mixed gas separation performance. When the propane volume fraction in the mixed gas was 24%, the inlet temperature was 25°C, and the inlet pressure was 0.20MPa, the permeation flux was 340.6L·m -2 ·h -1 , the separation factor for propane is 12.8.

Claims

1. A method for preparing a high-performance composite membrane that is easy to prepare on a large scale, characterized in that: The following steps are involved: (1) dissolving the hydroxyl-terminated PDMS in a soluble solvent to form solutions of different concentrations, and adding a crosslinking agent and a catalyst to prepare a casting solution; (2) using an ultrafiltration membrane as a support layer, coating the casting solution in step (1) on the support layer at a certain thickness, leaving it for a certain period of time to allow the solvent to evaporate and initially solidify; subsequently, coating the casting solution in step (1) on the initially solidified membrane at a certain thickness, leaving it for a certain period of time at room temperature to allow the solvent to evaporate and initially solidify, repeating this step for at least one time, and the concentrations of the casting solutions used in different batches of coating may be the same or different; (3) The membrane obtained in step (2) is heat treated for more than 0.5 hours to fully crosslink it to obtain a high-performance composite membrane.

2. The method for preparing a high-performance composite membrane that is easy to prepare on a large scale according to claim 1, characterized in that: The crosslinking agent used in the step (1) is ethyl orthosilicate, phenyltrimethoxysilane, octyltrimethoxysilane, n-octyltrichlorosilane, vinyltrimethoxysilane, methyltrimethoxysilane, γ-aminopropyltriethoxysilane or hydrogenated silicone oil.

3. The method for preparing a high-performance composite membrane that is easy to prepare on a large scale according to claim 1, characterized in that: The catalyst used in step (1) is an organotin catalyst.

4. The method for preparing a high-performance composite membrane that is easy to prepare on a large scale according to claim 1, characterized in that: The ultrafiltration membrane material used in the step (1) is any one of polyvinylidene fluoride, polytetrafluoroethylene, polysulfone, polyimide, polyetherimide, polyacrylonitrile or polyetheretherketone.

5. The method for preparing a high-performance composite membrane that is easy to prepare on a large scale according to claim 1, characterized in that: The heat treatment temperature in step (3) is between 40 and 120°C.